When Islamists Go into Politics - Hamzawy, Amr; Ottaway, Marina (Tufts Archival Research Center, 2005)
Volume 33, Issue 2. Fall Renowned scholars Amr Hamzawy and Marina Ottaway explore the impact of Islamists on politics-including the impact of this strategy on Islamist movements themselves. Hamzawy and Ottaway analyze the ideological and practical implications of Islamists' participation in democratic processes; they also discuss Islamists' participation in a range of contexts, from so-called "normal" conditions to siege and post-conflict elections.